Batasan Larangan Pekerjaan Lain Notaris Ditinjau Dari Pasal 17 Ayat (1) huruf I Undang-Undang Jabatan Notaris - Darmawan, Gusti Agung; Mayasari, I Dewa Ayu Dwi (Acta Comitas; Vol 8 No 03 (2023), 2023)
The purpose of writing this research is to provide an understanding of the views of the legal interpretation of other jobs regarding the prohibition of Article 17 paragraph (1) letter I of the Notary Office Law and the position of an authentic deed made by a Notary by having another prohibited job. The research method used by the author is normative law moving towards the blurring of norms. Review of the author's research based on the blurring of norms resulting from the ambiguity of other job sentences on the prohibition of the position of Notary as regulated in Article 17 paragraph (1) letter I of the Law on Notary Position Refer to primary legal sources that analyze the Notary Office and refer to legal sources secondary studies on scientific work and literature. Referring to writing techniques, namely by studying documents and then analyzing legal issues through deductive reasoning. The results show that the legal interpretation of other work is an act other than the skills of a person to become a Notary in order to be able to generate honorarium carried out according to a planned design with other parties, the work can lead to conflicts of interest and conflicts with his position. The position of an authentic deed made by a Notary by having another prohibited job is that it loses its authenticity until it is degraded into an underhanded deed because someone who made it has violated the prohibition in his position.